A mixed methods evaluation of medical tattooing for people who have experienced a burn injury - Rebecca Yeates; Ezinna Rospigliosi; Andrew R Thompson (SAGE Publishing, 2018)
Introduction: There are no existing studies examining the psychological merits of using facial medical tattooing (MT) following burn injury. This study evaluated an MT service supported by The Katie Piper Foundation. It examined accessibility, satisfaction and whether there were improvements in quality of life (QoL). Methods: Thirty-five service-users were invited to participate in a cross-sectional online survey. Twenty-five (71%) responded (24 women; age range = 21-64 years), and of these five (4 women; age range = 26-59 years) also participated in telephone interviews, which were analysed using descriptive thematic analysis. Findings: The service was largely considered easy to access (22/25) and convenient (25/25). Most service-users (22/25) were satisfied with the results of MT. Some areas of dissatisfaction were described, by a minority of service-users, including: the procedure being painful (1/25); the tattoo being below expectation or fading over time (3/25). The majority reported that MT had improved confidence (22/25); mood (19/25); and ability to socialise (19/25). The procedure improved some service-users' ability to carry out essential activities (14/25) and enjoyable activities (16/25). The qualitative responses provided during interview, indicated that all respondents found the procedure useful to their adjustment, although a minority (3/5) found it painful and also commented on fading (1/5). All described MT as contributing to a sense of increased normality. Conclusions: MT had the largest impact on emotional wellbeing and interpersonal domains of QoL. MT services should now improve awareness of the procedure, lobby for further support to provide wider access to the procedure, and routinely use measures assessing psychosocial outcomes.